2016
DOI: 10.1080/03007995.2016.1182901
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to antiplatelet treatment with P2Y12 receptor inhibitors. Is there anything we can do to improve it? A systematic review of randomized trials

Abstract: Antiplatelet therapy is the cornerstone of treatment for patients with acute coronary syndromes (ACS) and/or undergoing percutaneous coronary interventions. Non-adherence to medication after ACS may lead to increased morbidity, mortality, and costs to the healthcare system due to elevated risk of stent thrombosis, myocardial infarction or death. Medication adherence is an issue of growing concern regarding the improvement of health system performance. Promoting medication adherence offers a rare opportunity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 82 publications
1
49
0
Order By: Relevance
“…In several studies the age of patients was indicated as one of the factors affecting adherence to medication [8,14,[18][19][23][24]. Comorbidity burden increasing with age is associated with the necessity of polypharmacy.…”
Section: Determinants Of Non-adherencementioning
confidence: 99%
“…In several studies the age of patients was indicated as one of the factors affecting adherence to medication [8,14,[18][19][23][24]. Comorbidity burden increasing with age is associated with the necessity of polypharmacy.…”
Section: Determinants Of Non-adherencementioning
confidence: 99%
“…Nurse judgement of low discharge readiness was associated with a six-to nine-fold increase in readmission risk; however, patient self-assessment was associated neither with readmission nor with visits in emergency department [19]. Patient self-assessment is a purely subjective assessment, while nurse evaluation is more objective [20,21]. Such an approach was applied in RHD MIS in the first and second subscale.…”
Section: Discussionmentioning
confidence: 99%
“…The previously published RHD-MIS validation study showed a-Cronbach coefficient of 0.789, indicating a high level of reliability and homogeneity of the questionnaire [9]. The RHD-MIS consists of 23 questions divided into three subscales: subjective (1) and objective assessment of patient knowledge of the disease (2) and the patient's expectations (3).…”
Section: Methodsmentioning
confidence: 99%
“…Effective education should positively influence the patient's behaviour in reducing risk factors, self-control and adherence to prescribed pharmacotherapy [7,[9][10][11]. On the other hand, non-adherence to medical recommendations results in serious health and economic consequences [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%